High performance enzyme fuel cells using a genetically expressed FAD-dependent glucose dehydrogenase alpha-subunit of Burkholderia cepacia immobilized in a carbon nanotube electrode for low glucose conditions - Fapyane, Deby; Lee, Soo-Jin; Kang, Seo-Hee; Lim, Du-Hyun; Cho, Kwon-Koo; Nam, Tae-hyun; Ahn, Jae-Pyoung; Ahn, Jou-Hyeon; Kim, Seon-Won; Chang, In Seop (ROYAL SOC CHEMISTRY, 2013)
FAD-dependent glucose dehydrogenase (FAD-GDH) of Burkholderia cepacia was successfully expressed in Escherichia coli and subsequently purified in order to use it as an anode catalyst for enzyme fuel cells. The purified enzyme has a low K-m value (high affinity) towards glucose, which is 463.8 mu M, up to 2-fold exponential range lower compared to glucose oxidase. The heterogeneous electron transfer coefficient (K-s) of FAD-GDH-menadione on a glassy carbon electrode was 10.73 s(-1), which is 3-fold higher than that of GOX-menadione, 3.68 s(-1). FAD-GDH was able to maintain its native glucose affinity during immobilization in the carbon nanotube and operation of enzyme fuel cells. FAD-GDH-menadione showed 3-fold higher power density, 799.4 +/- 51.44 mu W cm(-2), than the GOX-menadione system, 308.03 +/- 17.93 mu W cm(-2), under low glucose concentration, 5 mM, which is the concentration in normal physiological fluid.